Moral decision making in sports: a case study on behaviors among Johor Sukma athletes / Nurul Sabrina Mohd Zain ... [et al.] - Mohd Zain, Nurul Sabrina; Ahmad, Mohamad Firdaus; Khaidzir, Mohd Fadhli Shah; Dahlan, Nur Dalilah; Bakri, Nur Hani Syazwani (Universiti Teknologi MARA, 2021)
Unethical decision-making among athletes has become a much-discussed topic in the sports world today. This practice is definitely caused by the lack of emphasis on sportsmanship and an overemphasis on the mentality of "winning at all cost" that motivates them to commit unethical conduct. The main objectives of this study were to determine the differences of the moral decision - making on behaviours among Johor SUKMA athletes based on gender. This study was carried out on 214 of Johor SUKMA athletes. The data were obtained through a questionnaire containing 24 items which was administered to measure the domains of athletes' moral decision-making in sports which covered acceptance of cheating, acceptance of gamesmanship and keeping winning in proportion. The Cronbach Alpha reliability coefficient value of the instrument was above 0.70 for each domain. The data was analysed using inferential analysis (Mann-Whitney Test). The findings showed that "keeping winning in proportion" was the main domain for the athletes' moral decision-making in sports and that there is no significance different in the mean score for the moral decision-making based on gender for the two domains which are "acceptance of cheating proportion" (p = 0.68 > 0.05) and "keeping winning in proportion" (p = 0.18 > 0.05). Meanwhile there is a significance different in "acceptance of gamesmanship" based on gender (p = 0.02 < 0.05). Thus, understanding about the moral decision-making among Johor SUKMA athletes may help Johor National Sports Council (MSNJ) and coaches to encourage a more positive decision-making towards sportsmanship conduct among athletes.